2021
DOI: 10.1007/978-3-030-86436-1_14
|View full text |Cite
|
Sign up to set email alerts
|

From Paper to Online: Digitizing Card Based Co-creation of Games for Privacy Education

Abstract: Education is rapidly evolving from co-located settings to remote and online learning. However, many proven educational tools are designed for collaborative, co-located classroom work. Effective sketching and ideating tools, such as card-based workshop tools, cannot be applied in remote teaching.This paper explores how the paper-based card and playboard metaphor can be digitized for remote student co-creation via video call sessions. Therefore, a card-based toolkit for co-creating educational games is transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A SG played to create other SGs is also referred to by some game studies scholars as Meta Serious Game [29]. The CGF is built on an action-oriented conception of the theory of affordances [30], [31] and exists in evaluated paper-based [11] and digital instances [12], [13].…”
Section: Research Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…A SG played to create other SGs is also referred to by some game studies scholars as Meta Serious Game [29]. The CGF is built on an action-oriented conception of the theory of affordances [30], [31] and exists in evaluated paper-based [11] and digital instances [12], [13].…”
Section: Research Objectivesmentioning
confidence: 99%
“…Considering the perspectives of the different stakeholders and engaging them in a roleplaying co-design activity can help to create such a balanced SG while offering it as a game that can provide sustainability during a project's developing research process [11], [12], [13]. It has been shown that a SG can bring together experts and novices and enable them to discuss about underlying domain challenges [6].…”
Section: Introduction 11 Background -Serious Games For Investigating ...mentioning
confidence: 99%
“…Some studies about co-# -will be assigned by editors. EVALUATING THE TRANSPOSITION OF A LEARNING ANALYTICS DASHBOARD CO-DESIGN TANGIBLE TOOL TO A DIGITAL TOOL 5 design (Goldman et al, 2019) uses both online activities and face-to-face time, and recent studies have analyzed the transposition of tangible tools into digital tools in other contexts (Jost & Divitini, 2021).…”
Section: Participatory Designmentioning
confidence: 99%